Epigenetic Regulation of Immune and Inflammatory Responses in Rheumatoid Arthritis - Chen, Qi; Li, Hao; Liu, Yusi; Zhao, Min (Frontiers in Immunology, 2022)
Purpose: Rheumatoid arthritis (RA) is a disease relevant to several environmental, genetic, and epigenetic factors which are heritable but reversible changes that affect gene expression without changing the primary DNA sequence. In this study, we aimed to comprehensively analyze epigenetic regulation in RA. Methods: Using the Gene Expression Omnibus database, we identified a methylation chip, RNA-sequencing, and miRNA microarray for RA. First, we searched for DNA methylation, genes, and miRNAs associated with RA using differential analysis. Second, we determined the regulatory networks for RA-specific methylation, miRNA, and m6A using cross-analysis. Based on these three regulatory networks, we built a comprehensive epigenetic regulatory network and identified hub genes. Results: Using a differential analysis, we identified 16,852 differentially methylated sites, 4877 differentially expressed genes, and 32 differentially expressed miRNAs. The methylation-expression regulatory network was mainly associated with the PI3K-Akt and T-cell receptor signaling pathways. The miRNA expression regulatory network was mainly related to the MAPK and chemokine signaling pathways. M6A regulatory network was mainly associated with the MAPK signaling pathway. Additionally, five hub genes were identified in the epigenetic regulatory network: CHD3, SETD1B, FBXL19, SMARCA4, and SETD1A. Functional analysis revealed that these five genes were associated with immune cells and inflammatory responses. Conclusion: We constructed a comprehensive epigenetic network associated with RA and identified core regulatory genes. This study provides a new direction for future research on the epigenetic mechanisms of RA.